PENCIPTAAN ALAM SEMESTA PERSPEKTIF AL-QUR’AN DAN SAINS (Studi Komparatif Tafsir Al-Azhar Dan Tafsir Al-Miṣbāḥ) - Muhammad Makrus (Journal Khafi : Journal Of Islamic Studies, 2023)
The universe which has a very orderly and complex arrangement is a sign of the power of its creator. The universe in which there is earth as a place of life for humans and at the same time as a place of death for humans is created according to human needs. Some people think that the universe was created because of the role of the creator, namely God, but some think that the universe was not created by the creator. Among these thinkers was Isaac Newton of the 17th-18th centuries with the theory "that the universe is classical" which means that there was no creation from the creator. Then what about the material origin of the universe, the method and process of its creation by the creator, then many theories emerged including the "big bang" theory which stated that the universe originated from super dense matter andhot. The purpose of this study is to find out the opinion of Hamka and Quraish Shihab regarding the verses of the universe in refuting western theories and to find out the origins of the formation of the universe according to tafsir-Azhar and al-Mishbah. This type of research islibrary research with the method of thematic interpretation. Data collection refers to the bookTafsīr with adābī ijtimāʻī pattern, namely Tafsīr al-Azhar by Hamka and Tafsīr al-Mishbah by Quraish Shihab. Data analysis uses interpretation and analysis methodscomparative.